Enantioseparation of Amino Acid Derivative on Quinine Carbamate Based Chiral Stationary Phase - FEGAS, R.; RIGHEZZA, M.; HAMDI, A. (Asian Journal of Chemistry, 2010)
A tert-butylcarbamoyl quinine based chiral stationary phase for direct enantiomer separation of amino acid was studied. The influence of mobile phase composition, methanol and different acids were systematically investigated to gain an insight into the overall chiral recognition mechanism.